2016
DOI: 10.1117/1.jbo.21.7.071106
|View full text |Cite
|
Sign up to set email alerts
|

Optical fiber-based full Mueller polarimeter for endoscopic imaging using a two-wavelength simultaneous measurement method

Abstract: Abstract. This paper reports a technique based on spectrally differential measurement for determining the full Mueller matrix of a biological sample through an optical fiber. In this technique, two close wavelengths were used simultaneously, one for characterizing the fiber and the other for characterizing the assembly of fiber and sample. The characteristics of the fiber measured at one wavelength were used to decouple its contribution from the measurement on the assembly of fiber and sample and then to extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…However, many studies revealed that linear retardance is largely dominant in biological tissues; indeed, polarimetric measurements performed on such tissues in backscattering configuration revealed that this type of structures exhibits very low circular retardance 1 , 13 , 40 , 41 . Consequently, R ≈ R L , and the Mueller matrix M R can be determined by 32 , 40 : where α is the orientation of one eigenaxis of the sample (also named “Azimuth” in this article), and can be determined using the following formula: …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many studies revealed that linear retardance is largely dominant in biological tissues; indeed, polarimetric measurements performed on such tissues in backscattering configuration revealed that this type of structures exhibits very low circular retardance 1 , 13 , 40 , 41 . Consequently, R ≈ R L , and the Mueller matrix M R can be determined by 32 , 40 : where α is the orientation of one eigenaxis of the sample (also named “Azimuth” in this article), and can be determined using the following formula: …”
Section: Methodsmentioning
confidence: 99%
“…Hence, the in vivo polarimetric systems presented to date are almost exclusively based on a relatively simple technique using Orthogonal State Contrast (OSC) 2 , 26 polarimetry. Several types of endoscopic polarimetric systems (needed for the exploration of inner cavities of the human body) have also been proposed in recent years 27 32 , but they have only been tested on ex vivo tissue samples. Very few in vivo Mueller polarimetric systems have been demonstrated and/or tested, such as one for studying the collagenase of mice 33 , and another for application in opthalmology for human patients 34 .…”
Section: Introductionmentioning
confidence: 99%
“…In this method, so-called "two-wavelength differential method (TWDM)", we simultaneously launch two probe beams at two very close wavelengths λ 1 and λ 2 in the fiber (Fig. 1) [19]. The beam at λ 1 is totally reflected by a dichroic mirror set at the output end of the fiber, making it possible to measure the Mueller matrix of this fiber only, on a round trip of the light.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover this polarimetric technique provides a macroscopic field of view (≈10 cm 2 ), and the delineation of suspicious areas can be imaged without any tissue contact. Through the integration of this technology into conventional instruments (e.g., colposcope, endoscope), polarimetric imaging is a promising tool for in vivo cancer detection and staging [8][9][10].…”
Section: Introductionmentioning
confidence: 99%